Anti-cancer effects of the extracts of broad and spirale cultivars of Codiaeum variegatum (L.) Blume on MCF-7, HepG2, and HeLa cell lines - Phanida Suphiratwanich; Benjaporn Buranrat; Supavadee Boontha (Shahrekord University of Medical Sciences, 2023)
Introduction: Codiaeum variegatum (L.) Blume is a well-known ornamental foliage plant used as a vegetable in northern Thailand, and it is the source of numerous bioactive substances. This work explored the effects of leaf extracts of broad (BCE) and spirale (SCE) cultivars of C. variegatum on three cancer cells, including human breast, human liver, and human cervical cancer cells. Methods: Ethanolic plant extracts were prepared, and then, 2,2-diphenyl-1-picryhydrazyl (DPPH), ferrous iron chelating, and lipid peroxidation assays were used to examine the flavonoid and phenolic compounds. The proliferative inhibition, growth, and migration of MCF-7, HepG2, and HeLa cancer cells, as a result of exposure to the extracts, were investigated. The extracts were investigated for their anti-cancer activities using sulforhodamine B (SRB), clonogenic, and wound-healing methods. Results: The data demonstrated that BCE and SCE contained high phenolic compounds. However, both extracts showed inactive anti-oxidant activities. Both extracts had high cytotoxicity on three types of cancer cells in a dose- and time-dependent manner after 24-72 hours of incubation with IC50 values in a range of 208-830 µg/mL. Moreover, the prepared extracts of C. variegatum significantly inhibited colony-forming ability and cell migration on all types of cancer cells. Compared with BCE, SCE showed more potent anti-cancer activities. Conclusion: These findings revealed that SCE had higher anti-cancer activities on MCF-7, HepG2, and HeLa cancer cells than BCE. Consequently, the SCE might be used as an effective chemotherapeutic compound for the prevention and treatment of cancer.